Young, Black and male : Exploring the intersections of racial and gender identity in an all-Black male high school - Rogers, Leoandra Onnie (New York University, 2012)
From popular culture to academia, there is national panic about the dismal life trajectories of Black males. This "Black male crisis" has contributed to emergent all-Black, all-male schools. Racial identity is commonly used to explain underperformance among Blacks, yet within-group gender disparity signifies the importance of gender relative to race. Minimal research exists on Black males' gender identities, and less on the intersections of gender and race. This longitudinal dissertation used quantitative and qualitative data to examine the development and intersections of racial and gender identity among Black adolescent males transitioning from co-educational grammar schools and entering the ninth grade at an all-Black, all-male high school. Findings are presented in two empirical papers. Paper 1 examined survey data collected from Black males (N = 183) to explain how boys' racial and gender identities were interrelated, changed over time, and influenced their psychological and academic adjustment. Results from the growth curve analysis revealed that boys' racial and gender identities were interrelated with each other and that higher levels of identity attachment were associated with better psychological and academic adjustment. Moreover, the strength of the relationship between gender identity and psychological adjustment increased over time, indicating that gender identity became increasingly important for boys' wellbeing. Paper 2 analyzed interview data with a subsample of Black males (n = 21) to examine how they resisted and accommodated racial and gender stereotypes. Results from the qualitative analysis revealed that boys were aware of the ways that racial and gender stereotypes overlap, but they responded to these stereotypes in different ways. Although some boys accommodated to both racial and gender stereotypes and others resisted these stereotypes, the majority of the boys responded by accommodating to gender stereotypes and resisting racial stereotypes. That is, they tended to perpetuate cultural stereotypes that require males to be the leader, emotionally stoic, and not to be feminine (i.e., gay) while challenging beliefs about the intellectual inferiority and incompetence of Black people. Findings are interpreted within the macro-context of cultural stereotypes and the micro-context of an all-Black male school. Implications for the study of identity, Black males, and single-sex education are discussed.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; adolescence; amériques; approches et analyses; chicago; discipline; genre; hommes* noirs; identité raciale; intersectionnalité; mémoires/thèses; philosophie; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; stéréotypes; étude longitudinale; étude qualitative; étude quantitative

Anti-Essentialism and Intersectionality - Grillo, Tina (Theorizing feminisms a reader, 2006)
'What is oppression ?' 'What should be done about it ?' Organized around these questions, Theorizing feminisms : a reader provides an overview of theoritical feminist writing about the quest for gender justice. Incorporating both classic and cutting-edge material, the reader takes into account the full diversity of women, highlighting the effects of race, ethnicity, nationality, class, sexuality, and religion on women's experience. Theorizing feminisms is organized into four sections and includes fifty-four essays. The first section introduces several basic concepts commonly employed when thinking about sexism - oppression, social construction, essentialism, intersectionality, gender, race, and class - and also raises questions about the perspective and legitimacy of the theorist. The second section surveys three approaches that attempt to characterize in a general way the source of injustice toward women : humanist feminism ('the sameness approach'), gynocentric feminism ('the difference approach'), and dominance feminism. Offering an alternate perspective, the third section introduces two 'localizing' approaches, grounded in postmodernism and identity politics, respectively. Skeptical of theories that attempt to analyze social phenomena across history and culture, authors in this section challenge, rather than answer, the text's organizing questions. The final section explores the relationship of feminism theory to three liberatory projects - postcolonialism, neo-materialism, and queer theory - that do not characterize themselves as feminist, yet take gender as a significant category of analysis. Each section opens with an introduction and each essay is followed by helpful study questions. the majority of the essays are presented in their entirety. Theorizing feminisms underscores the strong connection between feminist theory and practice by including essays that illustrate important political inspirations or applications of each theoritical approach. It also presents versions of the same approach from various points in history, revealing feminist theory to be dynamic and evolving, rather than static. Ideal for interdisciplinary courses in feminist theory, this volume will also serve as an invaluable reference for current and future generations of theorists."
Section: 1 vol. (XIX-564 p.) ; 24 x 19 cm
Keywords: 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; cours; discipline; essentialisme; intersectionnalité; justice sociale; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; thématiques; théorie féministe